EULAR recommendations for the management of systemic lupus erythematosus with neuropsychiatric manifestations: report of a task force of the EULAR standing committee for clinical affairs. Issue 12 (19th August 2010) - Bertsias, G K; Ioannidis, J P A; Aringer, M; Bollen, E; Bombardieri, S; Bruce, I N; Cervera, R; Dalakas, M; Doria, A; Hanly, J G; Huizinga, T W J; Isenberg, D; et al.
Abstract : Objectives: To develop recommendations for the diagnosis, prevention and treatment of neuropsychiatric systemic lupus erythematosus (NPSLE) manifestations. Methods: The authors compiled questions on prevalence and risk factors, diagnosis and monitoring, therapy and prognosis of NPSLE. A systematic literature search was performed and evidence was categorised based on sample size and study design. Results: Systemic lupus erythematosus (SLE) patients are at increased risk of several neuropsychiatric manifestations. Common (cumulative incidence >5%) manifestations include cerebrovascular disease (CVD) and seizures; relatively uncommon (1–5%) are severe cognitive dysfunction, major depression, acute confusional state (ACS), peripheral nervous disorders psychosis. Strong risk factors (at least fivefold increased risk) are previous or concurrent severe NPSLE (for cognitive dysfunction, seizures) and antiphospholipid antibodies (for CVD, seizures, chorea). The diagnostic work-up of suspected NPSLE is comparable to that in patients without SLE who present with the same manifestations, and aims to exclude causes unrelated to SLE. Investigations include cerebrospinal fluid analysis (to exclude central nervous system infection), EEG (to diagnose seizure disorder), neuropsychological tests (to assess cognitive dysfunction), nerve conduction studies (for peripheral neuropathy) and MRI (T1/T2, fluid-attenuating inversion recovery, diffusion-weighted imaging, enhanced T1 sequence). Glucocorticoids and immunosuppressive therapy are indicated when NPSLE is thought to reflect an inflammatory process (optic neuritis, transverse myelitis, peripheral neuropathy, refractory seizures, psychosis, ACS) and in the presence of generalised lupus activity. Antiplatelet/anticoagulation therapy is indicated when manifestations are related to antiphospholipid antibodies, particularly thrombotic CVD. Conclusions: Neuropsychiatric manifestations in SLE patients should be first evaluated and treated as in patients without SLE, and secondarily attributed to SLE and treated accordingly.